Factors Affecting Muzakki's Interest in Paying Zakat at Baznas City of Ternate - Alvira Panji Lestari; Suwito Suwito; Rinto Syahdan (International Ecsis Association, 2022)
This study aims to identify the impact accountability, transparency, income, the religiosity of interest in paying of Zakat to BAZNAS Ternate City. The population in this study is a type of personal Civil Server. As many as 150 respondents, the sample in this study was taken using a more purposive sampling technique or with the specific criteria. Data management in this study uses regression analysis using SPSS version 23. This study shows that accountability, transparency, income, and religiosity have a significant and positive impact on Muzaki’s interest in paying off Zakat on BAZNAS Ternate City.